Pengaruh Suka Bunga Bank Indonesia, Inflasi, dan Pendapatan Nasional Terhadap Nilai Tukar Rupiah di Indonesia Tahun 1997-2012 - Mahayanti, Putu Dewi; Sudirman, Wayan (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 3, No. 11, November 2014 (pp.485-548), 2014)
800x600 The purpose e of this research is to know w aboutinfluence e ofIndonesian n interest rate, inflation, and also national income toward Indonesian exchange rate between 1997-2012. This research is using secondary data that analized used linear regression method. The result is showing how Indonesian Interest rate, inflation, and national income have influence toward the exchange rate between 1997 - 2012 have a simultaneous influence.  However, in partial-side, there was insifnificant influence which is toward interest rate of Indonesia. Local Goverment is suggested to control the inflation degree to keep it stay on low-level, meanwhile e equilibrate standardization value of BI I Rate also needed for domestic economic actors, and government has to give more maximization in income even distribution to prevent the gap which able to make the strain issue among societies
Keywords: Indonesian Interest Rate, Inflation, National Income, Exchange Rate